A New Hybrid Highly Sensitive Optical Humidity Sensor - Ghadiry, M.; Ahmad, Harith; Lai, C.K.; Chong, W.Y.; Lee, S.H.; Tan, W.K.; Chu, K.K. (American Scientific Publishers, 2016)
An approach is presented to make new waveguide-based sensors aiming to improve the sensitivity. In this approach, the sensor benefits from both optical and electrical properties of the coated material on the waveguide. The approach was applied on graphene oxide for purpose of humidity sensing. The results show that the sensitivity is improved between 3% to 85% compared to optical device and 131% to 3600% compared to electrical device. More importantly, the new device shows at least 176% sensitivity at the whole range of relative humidity compared to 102% for an optical device. In addition, its fabrication process is fast, cheap and simple and the response and recovery times are very low, around 0.45 and 0.74 seconds respectively.